"On Expression, a Cosmic Phenomenon" 1925 (Translated by Giulia Gobbi) - Ortega y Gasset, José (Scenari, 2021)
In 1925, Ortega y Gasset publishes “Sobre la expresión, phenomenal cosmic”. In the opening words, the philosopher asks himself: what is a body? Is the body of an individual to be considered in the same way as any inanimate physical body with which we come into contact? Certainly not. While adopting the same term, we immediately realize that these are two terms that express distinct concepts. The Husserlian phenomenology – of which Ortegian philosophy nourishes in nuce – takes up the distinction between two terms of the German language, “körper” and “leib”. The first defines the body that lives, feels, and experiences, while the second term designates the mere body-as-object. For Ortega y Gasset, on the other hand, the body expresses the symbolic in its entirety, a signifier already signified, the complex and inseparable body-soul matrix, expression of a ‘cosmic phenomenon’.